1983
DOI: 10.1080/15287398309530353
|View full text |Cite
|
Sign up to set email alerts
|

Changes in humoral immunologic parameters after exposure to volcanic ash

Abstract: Occupational exposure to volcanic ash from Mount St. Helens continues during the salvaging of trees in the high dust blow-down area of Washington. We studied the effects of volcanic ash exposure on the level of humoral immune factors IgG, IgA, IgM, C3, C4, and ANA (antinuclear antibody) in a group of volcanic ash-exposed loggers shortly after the major eruption and one year later. Comparisons with similar levels in nonexposed, similarly employed, matched loggers were made. C3 and C4 levels were significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, it has been shown that physical immunologic barriers such as cilliary beating frequency and mucous lining can be altered after a short exposure to volcanic ash [33]. It has been reported that humoral immunologic parameters can also be affected by volcanic ash; for instance, workers exposed to volcanic ash had significantly lower C3 and C4 levels as well as marked decrease in serum IgG levels when compared to unexposed controls [34]. Immunological assays have shown that IgA, IgG, and albumin, airways proteins, play a protective role in mediating the effect of inhaled dust in human lungs [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that physical immunologic barriers such as cilliary beating frequency and mucous lining can be altered after a short exposure to volcanic ash [33]. It has been reported that humoral immunologic parameters can also be affected by volcanic ash; for instance, workers exposed to volcanic ash had significantly lower C3 and C4 levels as well as marked decrease in serum IgG levels when compared to unexposed controls [34]. Immunological assays have shown that IgA, IgG, and albumin, airways proteins, play a protective role in mediating the effect of inhaled dust in human lungs [30].…”
Section: Discussionmentioning
confidence: 99%
“…Toxicological studies have suggested that exposure to volcanic ash could also have a negative impact on immunological defense and could increase the occurrence of biological redox reactions [13], which could lead to more frequent infections and to organic damage [14] ( Table 2). In addition to the inherent physical and emotional disruptions caused by eruptive events, the economic impact of these events has severe consequences at a regional level because the people most impacted are those who belong to low-income groups.…”
Section: Introductionmentioning
confidence: 99%
“…In addition. the various types of potentially hazardous physical (traumatic), biological (infectious), and chemical (toxic) exposures which may result directly or indirectly from a disaster may require medical surveillance and environmental monitoring of high-risk groups (Bernstein et al, 1982;Buist et al, 1983;Fraunfelder et al, 1983;Olenchock et al, 1983). The biological plausibility and public health importance of both delayed and acute effects should be considered, since more sophisticated methods of recognition, evaluation and secondary prevention may be needed for health effects which may become manifest after a period of prolonged latency (Buist, 1982).…”
Section: Introductionmentioning
confidence: 99%